Algebra
posted by Micah
would the GCD for 42a^2 and 7a^5 be 7a?

drwls
Greatest Common Divisor? How about 7a^2? It goes into 7a^5 a^3 times and also goes into 42a^2 6 times
Respond to this Question
Similar Questions

algebra
here is my equation that I am struggling with (742a)(3/7) the 3/7 is a fraction. Just multiply 3/7 by each member of the term; i.e., 7(3/7)  (42a)(3/7)= 3 + (6a*3) = can you take it from here? 
college math question
Find the GCD of 24 and 49 in the integers of Q[sqrt(3)], assuming that the GCD is defined. (Note: you need not decompose 24 or 49 into primes in Q[sqrt(3)]. Please teach me . Thank you very much. The only integer divisor of both 24 … 
discrete math
If a and b are positive integers, prove that: ab = gcd(a,b)*lcm(a,b). Can visualize this being true and easily create examples just don't know how to prove algebraically. well the gcd of any two number can be found by multiplying the … 
coomon factors
I don't understand common factors. can someone show me how to find the greatest common factor of 385 and 1365? 
Algebra
GCF for the group of terms 42a^4, 7a^5 42a? 
Math
This is a problem concerning GCD. I need to prove gcd(a,b) = gcd(a,b+a). I always get like like halfway then hit a roadblock (e.g. i can prove gcd(a,b) <= gcd(a,b+a) but not gcd(a,b) >= gcd(a,b+a). 
math
(a). Is it true that for all set of positive integers a, b, c. gcd(a,c) + gcd(b,c) = gcd(a + b,c). Explain (b) Is it true that there exist a set of positive integers a,b,c, such that gcd(a,c) + gcd(b,c) = gcd(a + b,c). Explain 
math
GCD (24,20) IS 4. sINCE gcd(4,12 ) is 4 then GCD (24,2012 IS 4 USE Euclidem LGERITHM TO FIND THE gcd 722, 2413,209 
math!
GCD (24,20)IS 4. sINCE gcd (4,12) IS 4, THEN gcd (24,20,12) is 4. use this approach and the euclidean algorithim to find the GCD ( 722, 2413,209) WHAT IS THE gcd? 
Math
What is the inverse of 987x=1 (mod 11)? What I've done so far is: GCD(987, 11) 987 = 89 * 11 + 8 GCD(11, 8) 11 = 1 * 8 + 3 GCD(8,3) 8 = 2 * 3 + 2 GCD(3,2) 3 = 1 * 2 + 1 ...So basically, the GCD(987, 11) is 1. So... 1 = 3  2 = 3 